DAS: The Diabetes Awareness and Insight Scale. Issue 3 (May 2020) - Kim, Julia; Shah, Parita; Quilty, Lena C.; Caravaggio, Fernando; Plitman, Eric; Iwata, Yusuke; Pollock, Bruce G.; Dash, Satya; Sockalingam, Sanjeev; Graff-Guerrero, Ariel; Gerretsen, Philip
Abstract: Background and aims: Diabetes mellitus affects approximately 8.5% of the world's population with the majority of cases diagnosed with type 2 diabetes (T2DM). Impaired awareness or denial of T2DM is a common yet understudied construct that may negatively contribute to clinical outcomes. The aim of this study was to develop the Diabetes Awareness and Insight Scale (DAS), a self-report scale that measures illness awareness in persons with T2DM. Methods: Nine items were developed for the DAS that measure four domains of illness awareness, namely General Illness Awareness, Accurate Symptom Attribution, Awareness of Need for Treatment, and Awareness of Negative Consequences attributable to T2DM (www.illnessawarenessscales.com ). A total of 100 participants with a diagnosis of T2DM were recruited using a digital data collection platform. Results: The DAS demonstrated good convergent and discriminant validity, internal consistency, and one-month test-retest reliability. An exploratory factor analysis showed that the DAS exhibited three factors. Conclusions: Overall, the DAS is a novel and easy-to-administer scale that comprehensively measures subjective illness awareness in persons with T2DM. As the first scale of its kind, the DAS holds promise for use in epidemiology studies to examine the extent to which impaired illness awareness or illness denial contributes to clinical outcomes and T2DM management. Highlights: Impaired awareness of having type II diabetes mellitus may negatively contribute to clinical outcomes. This study presents the development and psychometric validation of the Diabetes Awareness and Insight Scale (DAS). The DAS is a novel self-report scale that measures subjective illness awareness. The DAS holds promise for use in epidemiology studies and treatment trials.